Drug History and SLE Laboratory Findings Among Iraqi Patients: A Hospital‐Based Study - Hashim Talib Hashim; Ahmed Dheyaa Al‐Obaidi; Mustafa Najah Al‐Obaidi; Hossam Tharwat Ali; Idris Sula; Hozifa Alfaki; Abdelrahim Elamin; Alaa Hamza Hermis; Assalah Othman; Ahmed Qasim Mohammed Alhatemi (Health Science Reports)
ABSTRACT Background and Aims Systemic lupus erythematosus (SLE) is a recurrent and remitting autoimmune disease that affects many organ systems. It is more common in women of reproductive age, with a 9:1 female preponderance. Due to the lack of data from developing countries, our study aims to provide comprehensive insights into the drug history and SLE laboratory findings among Iraqi patients. Methodology It is a cross‐sectional study at the Baghdad Medical Complex in Iraq. All SLE patients who attended the outpatient clinic between September and December 2022 were included. The patients included those who came for follow‐up, deterioration of their symptoms, or a first‐time diagnosis. Results SLE is much more prevalent among female patients. The ratio of female and male patients in our study was 19:1. This disease is more prevalent in the reproductive age group, with the mean age of our patients being 34 years, although the range spans from 15 to 85 years. The most prevalent signs and symptoms among the patients were photosensitivity (79.5%), hair loss (74%), and malar rash (72.5%). Most patients had positive antinuclear antibodies and anti‐double‐stranded DNA antibodies, with 73.5% and 65% testing positive, respectively. Conclusion In conclusion, this study represents an important step in exploring SLE within Iraq, providing invaluable insights into its management and laboratory findings. The findings contribute to the global understanding of SLE. This study underscores the significance of Iraq's genetic backgrounds and environmental conditions, which are different from those of other countries, in the process of enhancing the global medical literature and expanding our understanding of SLE patterns around the world.